How does washing without water perform compared to the traditional bed bath: a systematic review. Issue 1 (December 2017) - Groven, Fabian; Zwakhalen, Sandra; Odekerken-Schröder, Gaby; Joosten, Erik; Hamers, Jan
Abstract Background For immobile patients, a body wash in bed is sometimes the only bathing option. Traditionally, the bed bath is performed with water and soap. However, alternatives are increasingly used in health care. Washing without water is one such alternative that has been claimed to offer several advantages, such as improved hygiene and skin condition. This systematic review aims to provide a comprehensive overview of the evidence on outcomes of the washing without water concept compared to the traditional bed bath. Methods Controlled trials about washing without water outcomes published after 1994 were collected by means of a systematic literature search in CINAHL, Embase, MEDLINE, and PUBMED at the 25th of February, 2016. Additionally, references and citations were searched and experts contacted. Studies were eligible if (1) the study designs included outcomes of washing without water products developed for the full body wash compared to the traditional bed bath, and (2) they were controlled trials. Two researchers independently used a standardized quality checklist to assess the methodological quality of the eligible studies. Finally, outcomes were categorized in (1) physiological outcomes related to hygiene and skin condition, (2) stakeholder-related outcomes, and (3) organizational outcomes in the data synthesis. Results Out of 33 potentially relevant articles subjected to full text screening, six studies met the eligibility criteria. Only two studies (of the same research group) were considered of high quality. The results of these high quality studies show that washing without water performed better than the traditional bed bath regarding skin abnormalities and bathing completeness. No differences between washing without water and the traditional bed bath were found for outcomes related to significant skin lesions, resistance during bathing and costs in the studies of high quality. Conclusions There is limited moderate to high quality evidence that washing without water is not inferior to the traditional bed bath. Future research on washing without water is needed and should pay special attention to costs, hygiene, and to stakeholder-related outcomes, such as experiences and value perceptions of patients, nursing staff and family.